Helicobacter pylori Secreted Protein HP1286 Triggers Apoptosis in Macrophages via TNF-Independent and ERK MAPK-Dependent Pathways - Tavares, Raquel; Pathak, Sushil Kumar (Frontiers in Cellular and Infection Microbiology, 2017)
Macrophages constitute a powerful line of defense against H. pylori. The final disease outcome is highly dependent on the bacterial ability to modulate the effector functions of activated macrophages. Here, we report that H. pylori secreted protein HP1286 is a novel regulator of macrophage responses. Differential expression and release of HP1286 homologues were observed among H. pylori strains. Recombinant purified HP1286 (rHP1286) had the ability to bind to primary human monocyte-derived macrophages (MDM) and macrophage cell lines. Exposure to rHP1286 induced apoptosis in macrophages in a dose- and time-dependent manner. Although interaction of rHP1286 was observed for several other cell types, such as human monocytes, differentiated neutrophil-like HL60 cells, and the T lymphocyte Jurkat cell line, rHP1286 failed to induce apoptosis under similar conditions, indicating a macrophage-specific effect of the protein. A mutant strain of H. pylori lacking HP1286 protein expression was significantly impaired in its ability to induce apoptosis in macrophages. Significantly higher caspase 3 activity was detected in rHP1286-challenged macrophages. Furthermore, rHP1286-induced macrophages apoptosis was not inhibited in the presence of neutralizing antibodies against TNF. These observations indicate that rHP1286 induced a caspase-dependent and TNF-independent macrophage apoptosis. Pre-treatment of macrophages with U0126, an inhibitor of the ERK MAPK signaling pathway significantly reduced rHP1286-induced apoptosis. Furthermore, nuclear translocation of ERK and phosphorylation of c-Fos was detected in rHP1286-treated macrophages. These results provide functional insight into the potential role of HP1286 during H. pylori infection. Considering the ability of HP1286 to induce macrophage apoptosis, the protein could possibly help in the bacterial escape from the activated macrophages and persistence in the stomach.